Cost-Effectiveness of Repository Corticotropin Injection for the Treatment of Acute Exacerbations in Multiple Sclerosis - Hunter SF; Bindra J; Chopra I; Niewoehner J; Panaccio MP; Wan GJ (Dove Medical Press, 2021)
Samuel F Hunter,1 Jas Bindra,2 Ishveen Chopra,3 John Niewoehner,4 Mary P Panaccio,4 George J Wan4 1Advanced Neurosciences Institute, Franklin, TN, USA; 2Falcon Research Group, North Potomac, MD, USA; 3Manticore Consultancy, Bethesda, MD, USA; 4Mallinckrodt Pharmaceuticals, Hampton, NJ, USACorrespondence: George J WanMallinckrodt Pharmaceuticals, 53 I-78 Frontage Road, Hampton, NJ, 08827, USAEmail george.wan@mnk.comBackground: Relapses are common among patients with multiple sclerosis (MS) despite treatment with disease-modifying therapies. Repository corticotropin injection (RCI, Acthar® Gel), plasmapheresis (PMP), and intravenous immunoglobulin (IVIg) are alternative therapies for MS relapse. There is a dearth of economic assessments of these therapies for the acute exacerbations of MS. This study estimated the cost-effectiveness of RCI compared to PMP or IVIg.Methods: A Markov state-transition model compared outcomes (costs, relapses, remission, and utilities) with RCI versus PMP or IVIg for the acute exacerbations in MS. The model was developed from the United States (US) payer and societal perspectives over one to three years. Patients initiated on alternative therapies were evaluated in one-day increments for the first 30 days during treatment. The model assumes the natural history of MS after treatment in the first month, adjusting for the effect of treatment. Incremental cost-effectiveness ratios (ICERs) were estimated as cost per quality-adjusted life-year (QALY) gained. The uncertainty in model parameters was evaluated in probabilistic sensitivity analyses.Results: In the base case, RCI has an ICER of USD 42,078 per QALY compared to PMP over one year from the payer perspective and is dominant over two and three years; RCI is dominant compared to PMP from the societal perspective over all three years. Compared to IVIg, RCI is a dominant strategy from both payer and societal perspectives over all three years. Probabilistic sensitivity analysis supports the base case findings, suggesting that RCI may be cost-effective versus PMP and IVIg for acute exacerbations in MS.Conclusion: RCI is a cost-effective alternative treatment for MS relapses compared to PMP and IVIg from the US payer and societal perspectives.Keywords: Acthar® Gel, cost-effectiveness analysis, acute exacerbation, multiple sclerosis, quality-adjusted life-year, repository corticotropin injection